Comparative Study of Two Immunisation Protocols in Goats Using Thiol-Sepharose Chromatography-Enriched Extracts from Adult Haemonchus contortus Worms - Magnolia M. Conde-Felipe; José Adrián Molina; Antonio Ruiz; Otilia Ferrer; Mª Cristina Del Rio; Emma Carmelo; Juan R. Hernández-Fernaud; Francisco Rodríguez; José Manuel Molina (Vaccines)
Background: A comparative analysis was conducted between two immunisation protocols using different amounts of protein extracts from adult Haemonchus contortus worms, purified by thiol-Sepharose chromatography (625 μg/animal vs. 200 μg/animal). These protocols involved either five or two inoculations of the immunogen, respectively. Methods: To evaluate the level of immunoprotection, animals were challenged with L3 of H. contortus two weeks after the last inoculation of the immunogen and humanely sacrificed at 8 weeks post-infection. Parasitological, biopathological, and serological parameters were monitored through the experiment. Parasite burden, abomasal-specific antibody responses, and histopathological changes were determined at the end of the trial. Results: The immunisation protocols resulted in similar reductions in cumulative faecal egg counts (60.5–64.9%) and the total worm burden (47.5–50%) compared to non-immunized (control) animals. Overall, these parasitological data showed an early recovery of the haematocrit (PCV) after challenge in the immunised groups relative to control. Similarly, levels of H. contortus-specific IgG and IgA antibodies increased in both the serum and gastric mucus of immunised groups. Conclusions: These findings represent a further step towards the potential application of this type of immunogen under field conditions, as protective responses (associated with a reduction in faecal egg output) were achieved using a simplified protocol, with lower immunogen doses and fewer inoculations required to induce immunoprotection, thereby mitigating the pathological effects of the parasite and reducing its ability to spread and infect susceptible hosts.